Decentralised governance in water and sanitation in rural India - "Verma, Kush (ed.); Bist, B. S. (ed.); Cronin, Aidan (ed.)" (New Delhi, 2014)
Highlights the key discussion points and potential areas for strengthening the water, sanitation, and hygiene (WASH) governance processes in India.
Keywords: Decentralization inf government - India - Congresses